Overexpression of the Sorghum bicolor SbCCoAOMT alters cell wall associated hydroxycinnamoyl groups. - Hannah M Tetreault; Erin D Scully; Tammy Gries; Nathan A Palmer; Deanna L Funnell-Harris; Lisa Baird; Javier Seravalli; Bruce S Dien; Gautam Sarath; Thomas E Clemente; Scott E Sattler (PLoS ONE, 2018)
Sorghum (Sorghum bicolor) is a drought tolerant crop, which is being developed as a bioenergy feedstock. The monolignol biosynthesis pathway is a major focus for altering the abundance and composition of lignin. Caffeoyl coenzyme-A O-methyltransferase (CCoAOMT) is an S-adenosyl methionine (SAM)-dependent O-methyltransferase that methylates caffeoyl-CoA to generate feruloyl-CoA, an intermediate required for the biosynthesis of both G- and S-lignin. SbCCoAOMT was overexpressed to assess the impact of increasing the amount of this enzyme on biomass composition. SbCCoAOMT overexpression increased both soluble and cell wall-bound (esterified) ferulic and sinapic acids, however lignin concentration and its composition (S/G ratio) remained unaffected. This increased deposition of hydroxycinnamic acids in these lines led to an increase in total energy content of the stover. In stalk and leaf midribs, the increased histochemical staining and autofluorescence in the cell walls of the SbCCoAOMT overexpression lines also indicate increased phenolic deposition within cell walls, which is consistent with the chemical analyses of soluble and wall-bound hydroxycinnamic acids. The growth and development of overexpression lines were similar to wild-type plants. Likewise, RNA-seq and metabolite profiling showed that global gene expression and metabolite levels in overexpression lines were also relatively similar to wild-type plants. Our results demonstrate that SbCCoAOMT overexpression significantly altered cell wall composition through increases in cell wall associated hydroxycinnamic acids without altering lignin concentration or affecting plant growth and development.